Degradasi Zat Warna Methylene Blue dengan Katalis ZnO-CuO Menggunakan Metode Fotosonolisis - Nilam Nilam; Hary Sanjaya; Yohandri Yohandri (Jurnal Periodic Jurusan Kimia UNP, 2021)
Photosonolysis  method has been done to degrade Methylene blue in the solution. This study aims to determine the effect of radiation time and concentration of doping CuO. The absorbance of the samples was measured with a UV-Vis spectrophotometer. The maximum time to degrade Methylene blue using a ZnO catalyst was obtained at 120 minutes with percentage degradation 87,95%. The maximum doping concentration of CuO on the ZnO catalyst for 120 minutes was obtained at ZnO-CuO 20% catalyst with percentage degradation 90,33%. Analysis of catalyst characterization with a UV-DRS spectrophotometer obtained a band gap value of 3.30 eV.